The Politics of Extractivism: State Power and Business Interests on Coal Mining Industries in East Kalimantan, Indonesia and La Guajira, Colombia - Khurun'in, Irza (Department of International Relations, Universitas Brawijaya, 2026)
This article looks at the politics of coal mining in East Kalimantan in Indonesia and La Guajira in Colombia. The focus is on government power and business interests. In a Marxian theoretical framework, the study questions why coal mining persists in these regions and how government and business elites collaborate to exploit natural resources. The analysis is qualitative and comparative, with three main factors: government power, business interests, and local resistance movements. Documentary research and secondary sources are used to collect data on how coal extraction acts as an engine of economic growth at the same time as worsening social and environmental injustice. It stresses how these factors benefit global capitalist systems and spark resistance from marginalized communities. These two regions are compared throughout the research to increase the understanding of global extractivism patterns and their socio-political impact.